Delivering a Strategic Policy Framework to Protect Irish SMEs - Ó Domhnaill , Brian (Digital Repository of Theses - SSBM Geneva, 2024)
This research critically examines the role of small and medium-sized enterprises (SMEs) within the Irish economy, set against the backdrop of evolving global dynamics and the dominance of multinational corporations (MNCs). Despite Ireland's commendable economic performance, significant disparities between multinational and domestic sectors have emerged, exacerbated by events such as the COVID-19 pandemic. SMEs face considerable challenges, including restricted access to finance, rising business costs, low confidence, and inadequate government consultation. Findings indicate that many Irish SMEs experience severe financial constraints, with traditional banking channels often inaccessible for crucial investment projects. Elevated business costs, encompassing labor, rents, and utilities, further strain their operational capacities. Additionally, low confidence and insufficient governmental support contribute to a sense of marginalization among SMEs. The research recommends the establishment of a standalone state agency dedicated to SMEs. This agency would address SMEs' specific needs by providing a unified and strategic policy framework designed to foster growth, innovation, and resilience. By bridging existing gaps in the literature and proposing targeted policy interventions, the research offers actionable insights for policymakers and stakeholders. The proposed agency aims to enhance economic resilience, promote inclusive development, and mitigate vulnerabilities associated with overreliance on multinational corporations. By creating a supportive environment for SME growth, Ireland can more effectively support its domestic enterprises, ensuring sustainable economic development and reducing the disparities between multinational and domestic sectors.